Metaphors in Educational Videos - Michele Norscini; Linda Daniela (MDPI AG, 2024)
Traditionally, metaphors have been used as a pedagogical tool to facilitate the processes of educational mediation. From a medial perspective, there are various ways to implement educational mediation, and currently, we are witnessing an increase in the use of videos. Given the historical pedagogical role of metaphor and the widespread use of videos, we expected to find a significant amount of the scientific literature exploring metaphors in educational videos. However, studies establishing a direct connection are rare. Motivated by this gap, we decided to present users with a metaphorical educational video, intending to observe and analyze, through a phenomenological approach, how the metaphor is perceived by users. To gather data on users' experience, we applied the think-aloud protocol during video consumption and then we conducted semi-structured interviews. Subsequently, we analyzed the collected data using phenomenological procedures. Our results highlighted that the use of metaphor can stimulate engagement and facilitate the educational mediation, as long as the metaphor is shared and perceived as coherent by users. Finally, we have highlighted some distinctive aspects of using metaphor in educational videos, such as the ability to visually represent metaphors, create metaphorical contexts, and reinforce the processes of embodied simulation that occur during video viewing.